A Further Study Of The Recovery And Purification Of Surfactin From Fermentation Broth By Membrane Filtration - Mohd Hafez Mohd Isa; Richard A. Frazier; Paula Jauregi (Elsevier, 2024)
Surfactin is a bacterial lipopeptide produced by Bacillus subtilis and is a powerful surfactant, having also antiviral, antibacterial and antitumor properties. The recovery and purification of surfactin from com plex fermentation broths is a major obstacle to its commercialization; therefore, a two-step membrane filtration process was developed using a lab scale tangential flow filtration (TFF) unit with 10 kDa MWCO regenerated cellulose (RC) and polyethersulfone (PES) membranes at three different transmembrane pressure (TMP) of 1.5 bar, 2.0 bar and 2.5 bar. Two modes of filtrations were studied, with and without cleaning of membranes prior to UF-2. In a first step of ultrafiltration (UF-1), surfactin was retained effectively by membranes at above its critical micelle concentration (CMC); subsequently in UF-2, the retentate micelles were disrupted by addition of 50% (v/v) methanol solution to allow recovery of surfactin in the permeate. Main protein contaminants were effectively retained by the membrane in UF-2. Flux of permeates, rejec tion coefficient (R) of surfactin and protein were measured during the filtrations. Overall the three different TMPs applied have no significant effect in the filtrations and PES is the more suitable membrane to selec tively separate surfactin from fermentation broth, achieving high recovery and level of purity. In addition this two-step UF process is scalable for larger volume of samples without affecting the original functional ity of surfactin, although membranes permeability can be affected due to exposure to methanolic solution used in UF-2.